82‐1: Development of Full Roll to Roll Process for Flexible Display Backplane. Issue 1 (29th May 2019) - Kook, Yun Ho; Lee, HwanKeon; Choi, SungWoo; Kim, NamKook; Kim, ChulHo; Park, KwonShik; Yoon, SooYoung; Kang, InByeong
Abstract : In this article, we described a development of full Roll‐to‐Roll (R2R) process for flexible display backplane. For many years, we made an effort to convert rigid glass substrates to flexible films for thinness, light weight, flexibility and design freedom. Through Government support program, we have built and stabilized R2R facilities for many years. Amorphous indium‐gallium‐zinc oxide thin‐film transistors (TFTs) with coplanar structure are fabricated using roll type Polyimide film. We have demonstrated the world's first 20 inch flexible oxide TFTs backplane with SVGA (800x600, 50ppi) resolution), which can drive Electrophoretic paper. The process flow and key technologies to fabricate a‐InGaZnO flexible backplane by R2R process will be discussed.